CLINICAL AND PARACLINICAL CHARACTERISTICS OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE PATIENTS WITH METABOLIC SYNDROME TREATED AT THAI NGUYEN NATIONAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of chronic obstructive pulmonary disease (COPD) patient with metabolic syndrome, and to analyze the association between each component of metabolic syndrome and COPD severity according to the GOLD classification.Subjects and Methods: A cross sectional descriptive study was conducted on 109 COPD patients with metabolic syndrome who were treated as inpatients and outpatients at the Department of Respiratory Medicine, Thai Nguyen National Hospital, from August 2024 to August 2025.Results: The mean age of the study population was 69.23 ± 9.38 years, with males accounting for 89.9%. Common clinical symptoms included dyspnea and productive cough; frequent physical findings were reduced breath sounds and barrel chest. Most patients were classified as GOLD stage II–III. Chest X ray findings commonly showed emphysema and bronchial lesions. The most prevalent components of metabolic syndrome were hypertension (77.1%), hypertriglyceridemia (72.5%), and elevated fasting blood glucose (71.6%). The majority of patients had three components of metabolic syndrome (83.5%). Hypertension was associated with COPD severity according to the GOLD classification, with a statistically significant difference (p = 0.028). Conclusion: COPD patient with metabolic syndrome in this study were predominantly elderly males, with most classified as GOLD stage II–III. Hypertension, hypertriglyceridemia, and elevated fasting blood glucose were the most common components of metabolic syndrome; among these, hypertension showed a statistically significant association with COPD severity.
Keywords: Chronic obstructive pulmonary disease, metabolic syndrome, GOLD.